Phase Diversity-Based Fourier Ptychography for Varying Aberration Correction - Xiang, Meng; Pan, An; Liu, Jinpeng; Xi, Teli; Guo, Xin; Liu, Fei; Shao, Xiaopeng (Frontiers in Physics, 2022)
Fourier ptychography (FP) is geared toward efficiently creating high resolution images with large field of view. In the original illumination-based FP scheme, the aberrations in optical systems can be well reconstructed, which plays a prominent role in simple and compact optical arrangements. Unfortunately the reconstruction strategy for recoverying an optical system’s pupil function fails to consider the field-dependent nature of the pupil function in aperture-scanning FP scheme, which affects the quality of the reconstructed image to a certain extent. With this observation, we report a Phase-Diversity-based Fourier Ptychography (PDFP) scheme for varying aberration modeling. We image USAF resolution target with the proposed PDFP scheme, and demonstrate our ability to correct varying aberration and improve image quality. The reported approach allows aperture-scanning FP technology to use simpler optical systems for imaging, and may facilitate the further development of FP in practical applications such as industrial inspection and long-distance imaging.